Toward a better self-regulation: degree of certainty through fuzzy logic in a formative assessment. Issue 2 (May 2016) - Naji, A.; Ramdani, M.
Abstract In the present paper, we plan to introduce a new procedure for learner's assessment in the learning environment in a way true to reality by using fuzzy logic. In this evaluation, learner's responses are accompanied by a degree of certainty expressed by him. This method allows detection of problems encountered by the learner and also to fix the concepts mastered and those that are not. It is a diagnostic procedure that improves the process of content adaptation and self-adjustment on the one hand and makes the knowledge model clearly interpretable and more understandable to learner and tutor/teacher/head teacher on the other hand.